Russia and the Eastern Partnership: Loud criticism, quiet interest in cooperation - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2009)
On 7 May the Eastern Partnership initiative will be launched at a summit held in Prague under the auspices of the Czech EU Council Presidency. In addition to the twenty-seven EU heads of state and government, political leaders from Belarus, Ukraine, Moldova, Georgia, Armenia and Azerbaijan have also been invited to attend. The initiative represents a continuation of the European Neighbourhood Policy (ENP) as well as an intensification of its eastern dimension. A newcomer to the forum is Belarus, which the EU had not previously included in the ENP on account of its poor democratic record. The EU is still unclear about how extensive Russian involvement in the Eastern Partnership should be. The Russian government has commented harshly on the new EU initiative, yet Moscow seems willing in principle to participate in specific projects of the Eastern Partnership. How can these contradictory Russian attitudes be explained? And what repercussions are they likely to have for relations between the EU and Russia?
Keywords: 320